IMPLEMENTASI METODE MURAJA’AH DALAM MENGUATKAN HAFALAN QUR’AN PADA PROGRAM BACA TULIS QUR’AN DI SDS IT SULTHONIYAH SAMBAS TAHUN PELAJARAN 2023-2024 - Rapiza, Dewi Ferawati, Rona (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to find out and obtain information about the implementation of the murāja’ah method in strengthening Qur’an memorization in the Qur’an reading and writing program for class IV C students at SDS IT Sulthoniyah Sambas for the 2023-2024 academic year and to find out the implications of the murāja’ah method in strengthening Qur’an memorization an in the Qur’an reading and writing program for class IV C students at SDS IT Sulthoniyah Sambas for the 2023-2024 academic year. The results of the research concluded that the murāja’ah method in the Qur’an reading and writing program for class IV C students at SDS IT Sulthoniyah Sambas for the 2023-2024 academic year was carried out during literacy hours. Memorizing the Qur’an is carried out once a week, namely on Tuesdays. Every Tuesday, students are required to memorize at least one verse. the implications of the murāja’ah method in strengthening Qur’an memorization an in the Qur’an reading and writing program for class IV C students at SDS IT Sulthoniyah Sambas for the 2023-2024 academic year is that student Qur’an memorization becomes stronger and more maintained. This murāja’ah method can also improve students memorization of the Qur’an. So that there are several students whose memorization has exceeded the target set by the BTQ teacher.